Network pharmacology-based identification for therapeutic mechanism of Ling-Gui-Zhu-Gan decoction in the metabolic syndrome induced by antipsychotic drugs. (July 2019) - Xiang, Si-Ying; Zhao, Jing; Lu, Ying; Chen, Ru-Meng; Wang, Yan; Chen, Yi; Long, Bin; Zhu, Li-Ping; Yao, Pei-Fen; Xu, Yi-Feng; Chen, Jian-Hua
Abstract: Background: The metabolic syndrome (MetS) is a common side effect of second-generation antipsychotic drugs (SGAs), leading to poor prognosis in patients with mental illness. The traditional Chinese herbal formula Ling-Gui-Zhu-Gan decoction (LGZGD) is a clinically validated remedy for SGAs-induced MetS, but its underlying mechanism remains unclear. Methods: A network pharmacology-based analysis was performed to explore predicted plasma-absorbed components, putative therapeutic targets, and main pathways involved in LGZGD bioactivity. We constructed a target interaction network between the predicted targets of LGZGD and the known targets of MetS, after which we extracted major hubs using topological analysis. Thereafter, the maximum value of "edge betweenness" of all interactions was defined as a bottleneck, which suggested its importance in connecting all targets in the network. Finally, a pathway enrichment analysis of major hubs was used to reveal the biological functions of LGZGD. Results: This approach identified 120 compounds and 361 candidate targets of LGZGD. According to the data generated in this study, the interaction between JUN and APOA1 plays a vital role in the treatment of SGAs-induced MetS using LGZGD. Interestingly, JUN was a putative target of LGZGD and APOA1 is one of the known targets of both MetS and SGAs (olanzapine and clozapine). LGZGD was significantly associated with several pathways including PI3K-Akt signaling, insulin resistance, and MAPK signaling pathway. Conclusions: LGZGD might inhibit JUN and thereby increases the expression of APOA1 to maintain metabolic homeostasis via some vital pathways. Highlights: The targets of Ling-Gui-Zhu-Gan decoction (LGZDG), second-generation antipsychotic drugs (SGAs), and metabolic syndrome (MetS) overlap. LGZGD might cure SGAs-induced MetS through JUN-APOA1 interaction. LGZGD was significantly related to several pathways involved in MetS, such as PI3K-Akt, insulin resistance and MAPK pathway.